Cosmogenic Beryllium-7 in the Earth Atmosphere - E. A. Buraeva; V. S. Malyshevsky; V. I. Ratushny (Глобальная ядерная безопасность)
7Ве isotope is one of the few radionuclides, the content of which in the atmosphere does not depend on anthropogenic factors. Consequently, it can also be used as a monitor to identify sources of technogenic radionuclides entering the atmosphere such as emergency situations at radiation hazardous, chemically hazardous facilities. The article presents the results of monitoring the content of the 7Ве radioactive isotope in the surface atmosphere in the Rostov region for a ten-year period from 2001 to 2011, covering the second half of the 23rd and the first half of the 24th solar cycles. The data obtained confirm the inverse dependence of the average annual volumetric activity of 7Ве cosmogenic on solar activity. The observational data allowed for the first time to carry out a comprehensive study and to reveal correlations between the volumetric activity of 7Ве cosmogenic with the main meteorological parameters such as: air temperature, wind speed, precipitation, relative humidity and atmospheric pressure.